2016
DOI: 10.1186/s12889-016-2792-8
|View full text |Cite
|
Sign up to set email alerts
|

A transdisciplinary model to inform randomized clinical trial methods for electronic cigarette evaluation

Abstract: BackgroundThis study is a systematic evaluation of a novel tobacco product, electronic cigarettes (ECIGs) using a two-site, four-arm, 6-month, parallel-group randomized controlled trial (RCT) with a follow-up to 9 months. Virginia Commonwealth University is the primary site and Penn State University is the secondary site. This RCT design is important because it is informed by analytical work, clinical laboratory results, and qualitative/quantitative findings regarding the specific ECIG products used.MethodsPar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…A number of RCTs are currently underway investigating the efficacy of second-generation products 57,58. Data from these studies will not be available for several years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of RCTs are currently underway investigating the efficacy of second-generation products 57,58. Data from these studies will not be available for several years.…”
Section: Discussionmentioning
confidence: 99%
“…A number of RCTs are currently underway investigating the efficacy of second-generation products. 57 , 58 Data from these studies will not be available for several years. The onus will be on researchers to consider how they interpret their findings in the context of the EC landscape of the future.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected from a large US two-site randomized controlled trial evaluating the effects of e-cigs on toxicant exposure in smokers attempting to reduce their cigarette consumption (Clinical Trials identifier: NCT02342795). Details of the study can be found in Lopez et al 19 Only participants randomized to an e-cig condition were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…pregnancy, unstable serious medical or psychiatric conditions, or weekly or greater use of illegal drugs). Full inclusion/exclusion criteria have been published 11,12 and are available in the Supplement 1.…”
Section: Participantsmentioning
confidence: 99%
“…This report is based on exploratory analyses of a randomized placebo-controlled trial that was primarily designed to examine the effects of ENDS use on toxicant exposure in smokers. The methods and results for the primary toxicant outcome (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol, NNAL) have been reported elsewhere 11,12 .…”
Section: Introductionmentioning
confidence: 99%